Biodiversity of fungi in Rhizosphere of Imperata cylindrica on Toposequental landslide areas under dryland agriculture and agroforestry land use - Idsa Bela Islami; Sartohadi, Junun; Widada, Jaka; Bayu Dwi Apri Nugroho; Susandarini, Ratna; Jihan Dwi Islami; Purwaningsih, Rina; Hertiyana Nur Annisa; Mazaya, Amida; Vonihanitriniaina D.Z. Andriamanantena R. (Agriculture and Natural Resources, 2026)
Importance of the work: Soil erosion and land use affect fungal diversity, influencing soil fertility and ecosystem resilience in erosion-prone agricultural areas. Objectives: To assess fungal diversity in the rhizosphere of Imperata cylindrica (L.) P.Beauv. across erosion zones and land use systems on Sumbing Volcano, Central Java, Indonesia. Materials and Methods: Fungal communities were analyzed using DNA extraction, polymerase chain reaction, Illumina sequencing and glomalin-related soil protein quantification. The soil properties measured included the pH and nitrogen, organic carbon and phosphorus contents across agroforestry and dryland agricultural systems in different erosion zones. Results: In total, 164,221 high-quality sequences (99.7% of 164,650) identified an average of 359 operational taxonomic units per sample, grouped into the Ascomycota, Basidiomycota, Mortierellomycota and Glomeromycota. Agroforestry had higher levels of pH, nitrogen, organic carbon and phosphorus, whereas phosphorus was lower in dryland agriculture, particularly in depositional zones. Fungal diversity was higher in agroforestry (Chao index approximately 400, Simpson index approximately 0.88) than in dryland agriculture (Chao approximately 350, Simpson approximately 0.65). Clustering analysis showed the depositional zone samples (Ab and Cb) were distinct from the residual zone samples (Aa and Ca), reflecting soil and land use differences. Main finding: Agroforestry had enhanced fungal diversity and soil fertility, supporting sustainable agriculture in erosion-prone landscapes. These findings highlighted the role of land use in shaping microbial communities and ecosystem resilience.